PRELIMINARY REPORT ON THE CONTAMINATION CONTROL FOR CHEMICAL ANALYSES OF ANTARCTIC ICE SAMPLES - カナモリ, サトル; カナモリ, ノブコ; オサダ, カズオ; イサ, エリコ; ニシカワ, マサタカ; ワタナベ, オキツグ; ニシオ, フミヒコ; KANAMORI, Satoru; KANAMORI, Nobuko; OSADA, Kazuo; ISA, Eriko; NISHIKAWA, Masataka; et al. (National Institute of Polar Research, 1987)
P(論文) A possible penetration of contamination from the surface toward the inner part of cored ice and firn block samples was investigated for proper chemical analysis of Cl, SO_4,NO_3,NH_4,Na, K, Mg, Al, Fe, Ni, Cu, Zn and other elements. Generally, the contamination of the ice core sample remains within 10mm under the surface. However, for the elements with intense contamination, a high concentration level in the surface layer tends to affect the level in the inner part. For the firn block sample, though the contamination by Cl, SO_4,and NO_3 remains within 20mm of depth from the surface, NH_4,Na, K, Cu and Zn seem to pass through the surface layer but remain within 40mm. A thermal knife was constructed, for use in the laboratory, of nichrome wire of 1mm diameter covered with a platinum pipe, tested for cutting cored ice samples and was found satisfactory without significant contamination of the elements listed above. The use of a stainless steel hand saw was also found practical for firn block samples. departmental bulletin paper